A importância dos serviços ecossistêmicos prestados por abelhas em cultivos orgânicos de tomate: produção e incremento de polinizadores - Ferreira, Maria Cecilia de Carvalho Silva (2022)
The economic importance of pollinators, especially bees, is already recognized globally and the conservation of their local populations is increasingly urgent. The present study has the general objective of evaluating the bee population and the benefits of pollination in organic tomato crops in a buffer zone of a conservation unit; as well as doing an analysis on scientific dissemination about bees in Brazil in the last 10 years. The study was developed at the Associação de Agricultores BioDinâmicos da Serra do Rola Moça (AABD – Rola Moça), in Ibirité-MG, a rural property of organic and family farming, located in the surroundings of the Serra do Rola Moça State Park. Chapter 1 aimed to analyze the influence of pollination by Melipona quadrifasciata in protected organic tomato cultivation of the area. For this, the production and quality of fruits produced in open cultivation and protected cultivation were compared and showed differences, with tomatoes produced in the greenhouse having the highest values among the evaluated parameters. Chapter 2 aimed to understand the population of bees in the study site, expand knowledge about sampling bees using pan traps, evaluating how the colors of the traps and the tomato are discriminated by the bees. For this, we tested the efficiency of the most used colors in diversity studies, and, with a sampling effort of 6480 h, we collected 185 specimens of bees, concluding that the use of colored pan trap is an efficient methodology to estimate population and color preference of bees. Chapter 3 aimed to investigate the history and importance of national scientific dissemination for the general population and compare the number, type, language and theme of resources found in three scientific dissemination platforms, after searching with simple keywords (Bee and Brazil). This chapter arose from a personal interest in investigating Brazilian scientific dissemination in the current context of lack of credibility in the scientific community and misinformation among the population.